Simplified in vitro system for study of eukaryotic mRNA translation by measuring di- and tripeptide formation. - Cenatiempo, Y (1983)
An in vitro system for measurement of rabbit globin mRNA translation has been developed based on the formation of the NH2-terminal dipeptide, fMet-Val. The basic components include a partially purified initiation factor preparation from rabbit reticulocytes supplemented with eukaryotic initiation factor 4A, purified and formylated yeast Met-tRNAi, and rabbit liver or Escherichia coli Val-tRNA1Val. Picomole quantities of fMet-Val are synthesized, dependent on mRNA, and the dipeptide is readily assayed by a simple extraction procedure. In the presence of Leu-tRNA or His-tRNA, the tripeptides fMet-Val-Leu and fMet-Val-His are synthesized, corresponding to the NH2-terminal sequence of alpha- and beta-globin, respectively. Therefore, tripeptide synthesis provides a simple means to distinguish between the expression of the alpha- and beta-globin mRNA species.